Breastfeeding among Latino Families in an Urban Pediatric Office Setting - Elizabeth Sloand; Chakra Budhathoki; Julia Junn; Dolly Vo; Victoria Lowe; Amy Pennington (Nursing Research and Practice)
Objective. To determine the breastfeeding rate of Latino infants at an urban pediatric clinic in the first six months of life and to identify factors associated with breastfeeding. Methods. Investigators conducted a retrospective chart review of infants seen at the clinic in 2014 as part of a mixed methods study. Topics reviewed included demographics, infant health data, and feeding methods at 5 points in time. Bivariate correlations and cross-tabulations explored associations between variables. Results. Most of the mothers (75%) fed their newborns with both breastfeeding and formula (las dos). At 6 months, a majority were formula-fed only (55.9%). Approximately 10% of mothers exclusively breastfed their newborns, and the trend of exclusive breastfeeding remained steady through the 6-month visit. Over time, the number of mothers who exclusively bottle-feed their infants steadily rises. There were no statistical differences among the feeding method groups with regard to birth order of child, number of adults or children in the household, vaccination rate, number of sick visits, or infants’ growth. Conclusions. More targeted attention to this population and other immigrant populations with culturally tailored interventions spanning the prenatal to early infancy periods could increase exclusive breastfeeding and ultimately improve child health.